1974
DOI: 10.1152/ajplegacy.1974.226.2.397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol on active transport in the dog stomach

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

1975
1975
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Thus, when the mucus-bicarbonate barrier protecting the epithelial cells is im paired, ethanol can directly attack the denudated epithelium and promote also intracel lular penetration of other molecules. On the other hand ethanol was shown to inhibit transport of ions such as chloride [30,31] and sodium [30,32], the latter being an event occurring at alcohol concentrations of 6% or more [28], It has been suggested that inhibition of active Na+ transport leads to intracellular accumulation of sodium, an ions and water. The consequent swelling of epithelial cells would produce cellular dis ruption with increased permeability of the mucosa [30,32],…”
Section: Increased Mucosal Permeabilitymentioning
confidence: 99%
“…Thus, when the mucus-bicarbonate barrier protecting the epithelial cells is im paired, ethanol can directly attack the denudated epithelium and promote also intracel lular penetration of other molecules. On the other hand ethanol was shown to inhibit transport of ions such as chloride [30,31] and sodium [30,32], the latter being an event occurring at alcohol concentrations of 6% or more [28], It has been suggested that inhibition of active Na+ transport leads to intracellular accumulation of sodium, an ions and water. The consequent swelling of epithelial cells would produce cellular dis ruption with increased permeability of the mucosa [30,32],…”
Section: Increased Mucosal Permeabilitymentioning
confidence: 99%
“…the mechanism of action of this agent. They include reduced gastric blood flow (3), disruption of the so-called gastric mucosal barrier (4,5), accompanied by bicarbonate leakage (6), as well as metabolic alterations deeply linked to the acid secretory activity in the damaged gastric mucosa (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Inhibition of the active transport of chloride in the rat stomach by topical application of 20% ethanol has been demonstrated (1). Studies conducted on the isolated (2) and intact dog stomach (3) have also demonstrated inhibition of active ion transport and acid secretion. A model for active chloride transport has been described by Kasbekar and Durbin (4) which is operative through a bicarbonate-stimulated ATPase, coupling chloride movement with bicarbonate in a manner similar to ATPase-activated sodium and potassium transport.…”
mentioning
confidence: 99%